Komposisi Karawitan Tabuh Petegak Kreasi “Sarwa Luwih ” - Biagi, Gede Nikolas Candra; Sudirga, I Komang; Yulianti, Ni Ketut Dewi (Pusat Penerbitan LPPMPP ISI Denpasar, 2025)
Joged Bumbung art, particularly in Buleleng Regency, faces challenges in maintaining its appeal among the community. This is due to the dominance of the classic style, which is considered less attractive to the younger generation, who are more interested in a contemporary version of Joged Bumbung. In this context, this article discusses the creation of a percussion composition, the petegak pejogedan, by Sarwa Luwih through the MBKM Independent Study/Project Program. This work is an innovative effort to revive the classic Joged Bumbung art. The petegak pejogedan, a composition played before the Joged Bumbung performance begins, generally still uses the traditional style from the 1970s. However, there is a trend of decreasing interest in this style, despite its significant historical value in classical Joged Bumbung performances. Through this work, the author aims to create a new composition that combines traditional elements with innovation, such as incorporating the Karinding and Bumbung Genggong musical instruments, which have not previously been found in Joged Bumbung percussion.